Morphological Classification and Facet-Based Typing of Human Left Patella - A Descriptive Skeletal Study in a Bangladeshi Population (The Planet, 2025)
Background: The patella is the largest sesamoid bone, crucial for knee joint biomechanics, yet little is known about its morphometry and facet-based classification in the Bangladeshi population. The current study aimed to evaluate sex-based morphometric differences and facet classification of the human left patella in a Bangladeshi skeletal sample. Methods & Materials: A total of 150 dry, fully ossified left patellae were analyzed. Linear dimensions (height, width, thickness, and facet widths) and derived ratios (width-to-height, width-to-thickness, height-to-thickness, facet ratios) were recorded. Sex was estimated using discriminant function analysis. Patellae were classified into Types A, B, and C based on articular facet widths. Statistical comparisons were performed using unpaired t-tests (p
Keywords: Patella morphometry; Facet classification; Sexual dimorphism; Bangladeshi population; Orthopedic anatomy